2018
DOI: 10.2138/am-2018-6554
|View full text |Cite
|
Sign up to set email alerts
|

Carbonic acid monohydrate

Abstract: In the water-carbon dioxide system, above a pressure of 4.4 GPa, a crystalline phase consisting of an adduct of the two substances can be observed to exist in equilibrium with the aqueous fluid. The phase had been found to be triclinic, and its unit cell parameters determined, but the full crystalline, and even molecular, structure remained undetermined. Here, we report new diamondanvil cell, x-ray diffraction data of a quality sufficient to allow us to propose a full structure. The crystal exists in the P1 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 42 publications
(47 reference statements)
1
14
0
Order By: Relevance
“…The oxidized ocean may have been reduced in time with hydrogen generated by serpentinization enabled by thermal cracking (Vance et al., 2016), but better constraints on the conditions of fracture formation and propagation are required (Klimczak et al., 2019). Further improvements to the thermodynamic data of high pressure H2normalOCO2 phases (Abramson et al., 2018) and their integration with thermodynamic models (e.g., Perple_X) are also needed to assess the build‐up of the ocean: the stability of such phases can be the factor dictating whether an ocean world will be habitable (Marounina & Rogers, 2020). Finally, we have also made the simplifying assumption that fluid percolation from depth was efficient.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The oxidized ocean may have been reduced in time with hydrogen generated by serpentinization enabled by thermal cracking (Vance et al., 2016), but better constraints on the conditions of fracture formation and propagation are required (Klimczak et al., 2019). Further improvements to the thermodynamic data of high pressure H2normalOCO2 phases (Abramson et al., 2018) and their integration with thermodynamic models (e.g., Perple_X) are also needed to assess the build‐up of the ocean: the stability of such phases can be the factor dictating whether an ocean world will be habitable (Marounina & Rogers, 2020). Finally, we have also made the simplifying assumption that fluid percolation from depth was efficient.…”
Section: Discussionmentioning
confidence: 99%
“…H O E -2 CO E phases (Abramson et al, 2018) and their integration with thermodynamic models (e.g., Perple_X) are also needed to assess the build-up of the ocean: the stability of such phases can be the factor dictating whether an ocean world will be habitable (Marounina & Rogers, 2020). Finally, we have also made the simplifying assumption that fluid percolation from depth was efficient.…”
mentioning
confidence: 99%
“…It was even possible to sublime and re-condense the solid. While the activation barrier of the exothermic monomolecular decay, H 2 CO 3 → CO 2 + H 2 O, is as large as 2 eV, the process becomes auto-catalyzed by the water molecules (Hage et al, 1998 ; Loerting et al, 2000 ; Abramson et al, 2018 ).…”
Section: The Periodic Table As a Blinker As Well As An Eye-openermentioning
confidence: 99%
“…Abramson et al (2017) identified the presence of a stable solid phase in the H 2 O-CO 2 system for P > 4.4 GPa. Abramson et al (2018) then determined that this phase consists of a monohydrate of carbonic acid, measured its crystalline structure and derived its density at P = 6.5 GPa and T = 413.15 K.…”
Section: Monohydrate Of Carbonic Acidmentioning
confidence: 99%
“…The H 2 O-CO 2 phase diagram is poorly characterized at pressures above ∼1 GPa. A recent discovery is the formation of a carbon-bearing solid at high temperatures and pressures: the monohydrate of carbonic acid (H 2 CO 3 • H 2 O) (Abramson et al 2017;Abramson et al 2018). Abramson et al (2017) identified the presence of a stable solid phase in the H 2 O-CO 2 system P > 4.4 GPa.…”
Section: Monohydrate Of Carbonic Acidmentioning
confidence: 99%